Investigação da expressão gênica diferencial em resposta aos efeitos da proteína anti-inflamatória Anexina A1 nas células de carcinoma de colo de útero - Prates, Janesly [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Carcinoma of the cervix, also called cervical cancer is the second most common cancer in women worldwide and is the fourth leading cause of death in developing countries. The cervical carcinogenesis is related to genetic alterations, infection with Human Papillomavirus (HPV), angiogenesis and inflammation. The idea that inflammation is involved in tumorigenesis is supported by the observation that often arises in areas of chronic inflammation. Furthermore, the inflammatory response is controlled by the action of anti- inflammatory mediators that act to maintain homeostasis of the immune response and prevent tissue damage. Among these mediators is included annexin A1 (ANXA1), a protein of 37 kDa, which is expressed by tumor cells and acts as a modulator of the inflammatory process. Given these considerations, we investigated in vitro the influence of this protein in SiHa cells on the morphology, proliferation and gene and protein expression. In order to realize this aim, the cell line SiHa was cultured in complete medium and treated with the peptide ANXA1Ac2 -26 to evaluate the effect of this protein on times 2, 4, 24, 48 and 72 hours in morphology and cell proliferation. The results showed that the peptide did not alter the morphology of SiHa cells, but decreased cell proliferation, indicating the time 72 hours as the most significant by statistical analysis, followed by a further cultivation for subsequent ultrastructural immunocytochemical analysis, RNA extraction, and development of technical Rapid Subtractive Hybridization (RaSH). The validation of six differentially expressed genes was performed by quantitative real-time PCR (RT- qPCR). The expression of ANXA1 was decrease in cells treated with the peptide observed by ultrastructural immunocytochemical analysis. The RaSH technique resulted in 82 differentially expressed genes after treatment with ANXA1Ac2 -26. Six of these genes (HIF1A, ID1, LDHA, NCOA3, RAB13, TPT1), because their ...

O carcinoma de colo de útero, também denominado câncer cervical, é o segundo tipo de câncer mundialmente mais frequente em mulheres, sendo a quarta causa de morte em países em desenvolvimento. A carcinogênese de colo de útero está relacionada com alterações genéticas, infecção pelo Papilomavirus Humano (HPV), angiogênese e processos inflamatórios. A idéia de que a inflamação está envolvida na tumorigênese é apoiada pela observação de que surge frequentemente em áreas de inflamação crônica. Por outro lado, a resposta inflamatória é controlada pela ação de mediadores anti-inflamatórios, que atuam para manter a homeostasia da resposta imunológica e prevenir a lesão tecidual. Entre esses mediadores destacamos a anexina-A1 (ANXA1), proteína de 37 kDa, que é expressa pelas células tumorais e atua como moduladora do processo inflamatório. Diante dessas considerações, investigamos, in vitro, a influência dessa proteína nas células SiHa sobre a morfologia, proliferação e expressão gênica e proteica. Para isso foi cultivada a linhagem celular SiHa em meio completo e tratada com o peptídeo ANXA1Ac2-26 para avaliar o efeito dessa proteína nos tempos de 2, 4, 24, 48 e 72 horas na morfologia e proliferação celular. Os resultados mostraram que o peptídeo não alterou a morfologia das células SiHa, no entanto diminuiu a proliferação celular, evidenciando o tempo de 72 horas como o mais significante pelas análises estatísticas, seguido de um novo cultivo para posterior análise imunocitoquímica ultraestrutural, extração de RNA e desenvolvimento da técnica de Hibridização Subtrativa Rápida (RaSH). A validação dos seis genes diferencialmente expressos foi realizada por PCR quantitativo em tempo real (RT-qPCR). A expressão da proteina ANXA1 foi observada diminuida nas células SiHa tratadas com o peptídeo pelas análises imunocitoquímicas ultraestruturais. A técnica de RaSH resultou em 82 genes ..
Keywords: Genética; Expressão gênica; Colo uterino - Câncer; Anexina A1; Reação em cadeia de polimerase; Gene expression